Identification of Heavy Metal Concentration in Citarum River Water Using the Heavy Metal Pollution Index Method - Wardhani, Eka; Wulan, Diana Rahayuning; Velda, Nazla Amaliyah; Nugraha, Willy Cahya; Rohman, Oman; Irmansyah, Athaya Zahrani (Universitas Diponegoro, 2024)
The Citarum River is the largest and longest river in West Java Province. The basin in that location has influenced by human activities and the industrial sector. One of the hazardous pollutants contained in industrial wastewater is heavy metals. This study aims to identify the content of dissolved heavy metals (Fe, Cd, Cr, Cu, Hg, Pb, and Zn) in Citarum River water, Purwakarta Regency, at three observation points, namely Jatiluhur Reservoir Outlet, Cilalawak Bridge, and Cilele Bridge. The Atomic Absorption Spectrophotometry Method is used to analyze the dissolved heavy metals. Determination the level of metal contamination using the Heavy Metal Pollution Index (HPI) method. The study results that three metals exceeded the standard based on Government Regulation 22 of 2021 Class II, namely Fe, Hg, and Zn. Fe metal in the range between 0.277-1.179 mg/L, Hg metal between 0.011-0.100 mg/L, and Zn metal between 0.017-0.074 mg/L. HPI analysis showed that at three points in both sampling periods, it indicated that heavy metals highly polluted river water because the results obtained exceeded the HPI pollutant index, which was > 100. The biggest contribution of dissolved heavy metals in the Citarum River water body was dominated by the Hg parameter